2004
DOI: 10.2139/ssrn.571961
|View full text |Cite
|
Sign up to set email alerts
|

House Price Efficiency: Expectations, Sales, Symmetry

Abstract: An efficient housing market is of critical importance for individual welfare and for a well-functioning economy. We test the efficiency of this market by estimating the factors that determine both the long-run and the dynamic paths of regional house prices. Our tests use a new quarterly regional panel data set covering the 14 regions of New Zealand from 1981 to 2002. The tests indicate that regional housing markets converge to an equilibrium consistent with consumer optimising conditions, and hence with long-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The logically next stage is to carry out multivariate work. This would complement the long-run and dynamic adjustment process work reported in Grimes, Aitken and Kerr (2004) referred to in our Introduction, and in which regional economic activity, the expected real user cost of capital, the regional housing stock, and an asymmetric influence of regional house sales activity were all found significant.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The logically next stage is to carry out multivariate work. This would complement the long-run and dynamic adjustment process work reported in Grimes, Aitken and Kerr (2004) referred to in our Introduction, and in which regional economic activity, the expected real user cost of capital, the regional housing stock, and an asymmetric influence of regional house sales activity were all found significant.…”
Section: Discussionsupporting
confidence: 69%
“…In Grimes, Aitken and Kerr (2004), from OLS and SUR regressions of panel data, for 14 economic regions over the period 1981q1 to 2002q4, it was concluded that for long run New Zealand a 1 percent increase in 1 Our classification is therefore less restrictive than that used in the IMF's (2003) investigation of asset price booms and busts for 19 industrial countries in the postwar period. They define house price booms as large and persistent increases, which begin with a peak and end with the subsequent peak, i.e.…”
Section: Introductionmentioning
confidence: 91%
“…In fact, earlier researchers have focused on concepts like housing market efficiency and rationality of forecasts. For example, Grimes et al [5] study housing market efficiency and overshooting of house prices based on regional data for New Zealand. Song et al [6] and Aggarwal and Mohanty [7] analyze the rationality of forecasts of U.S. housing starts published in the Money Market Services.…”
Section: Introductionmentioning
confidence: 99%
“…That model was adapted by Grimes et al (2004) to model long-run and short-run house price determinants at RC level in New Zealand using data available at that level of disaggregation. As described in Section 0 of this paper, our TLA data is more refined than that available for the RC study; we have adapted the Pain and Westaway framework to suit the data at hand.…”
Section: Theoretical Structurementioning
confidence: 99%
“…6 In particular, it builds on Grimes et al (2004), which estimates the determinants of house prices at a Regional Council (RC) level within New Zealand. It is also substantially informed by the TLA and RC time series work in Grimes et al (2004). In our structural modelling (Section 4), we adopt a similar theoretical approach to the former study.…”
mentioning
confidence: 99%